(untitled) (Journal of Universal Science Research, 2024)
This paper studies methods of lead and zinc metal ions extraction by dithizone from Khondzha wastewater samples. Inorganic metals or ions can act back with dithizone to produce colourful coordination. The dithizone reagent is highly sensitive to the presence of heavy metals such as lead (Pb) and zinc (Zn) as designated in this study. Inorganic metals or ionic can react with dithizone to produce coloured coordination compounds. As a result of studying the "composition-structure-property" system in chemical compounds, it is possible to theoretically predict the properties, composition and molecular structure of complex compounds during research. Such information helps to synthesize complex compounds with selected properties, composition and structure. Creating the basis of theoretical studies of the formation of complex compounds and the possibility of their practical application is one of the urgent problems of the chemistry of coordination compounds in the advanced period of modern science.